2014
DOI: 10.1039/c3cp55039g
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing nanoporous materials for gas storage

Abstract: aIn this work, we address the question of which thermodynamic factors determine the deliverable capacity of methane in nanoporous materials. The deliverable capacity is one of the key factors that determines the performance of a material for methane storage in automotive fuel tanks. To obtain insights into how the molecular characteristics of a material are related to the deliverable capacity, we developed several statistical thermodynamic models. The predictions of these models are compared with the classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
121
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 46 publications
(97 reference statements)
1
121
0
Order By: Relevance
“…The bulk material is then represented with a close packing of spheres as in Figure 4C, a modeling scheme previously proposed for analysis of PAF materials. 48 Because the carbon atoms of a shell are shared between multiple adsorption pockets, we define, as an approximation, the unit cell of our material as the sphere of radius R. We analyzed zeolites in the context of this model in our previous work 49 to capture a correlation between enthalpy and entropy change upon adsorption.…”
Section: Evaluating Ppns For Methane Storagementioning
confidence: 99%
See 2 more Smart Citations
“…The bulk material is then represented with a close packing of spheres as in Figure 4C, a modeling scheme previously proposed for analysis of PAF materials. 48 Because the carbon atoms of a shell are shared between multiple adsorption pockets, we define, as an approximation, the unit cell of our material as the sphere of radius R. We analyzed zeolites in the context of this model in our previous work 49 to capture a correlation between enthalpy and entropy change upon adsorption.…”
Section: Evaluating Ppns For Methane Storagementioning
confidence: 99%
“…52 In our previous work, we showed that there is indeed an optimal heat of adsorption but that it depends on the pore size. 49 Second, the free volume in the material increases with increasing pore size because the carbon atoms in the shells take up a lesser fraction of the space occupied by the bulk material ( Figure S4a in the SI).…”
Section: Evaluating Ppns For Methane Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Methane storage capacity is by far the most studied sorption property in the field of computational high throughput screening of nanoporous materials [27][28][29][30][31][32][33][34][35][36][37]83 . There are several reasons for this, the first being that there is considerable interest in safely and efficiently storing methane for use as an alternative, clean-burning fuel in motor vehicles.…”
Section: H2 Methane Storagementioning
confidence: 99%
“…Here, computational discovery is typically the first step, always to be followed by experimental work. It would seem obvious to adopt a similar strategy for nanoporous materials design, and sure enough in the past 5 years we have witnessed the proliferation of studies on virtual high-throughput screening of porous materials for gas capture and storage applications [27][28][29][30][31][32][33][34][35][36][37] .…”
mentioning
confidence: 99%